Preparação de um Sinton Funcionalizado a Partir da Carvona Visando a Síntese de alfa-metileno-gama-butirolactonas Monoterpênicas - dos Santos, Reginaldo Bezerra; César, Roberta Cecília Vettoraci; Lacerda Jr., Valdemar; Greco, Sandro José; Cunha Neto, Alvaro (Orbital: The Electronic Journal of Chemistry, 2015)
(R)-(-)-Carvone (6) has been transformed into oxygenated derivative 13, which is expected to be a useful synthon or chiral template in the synthesis of natural a-methylene-g-butyrolactones. This synthesis of compound 13 involves classics reactions of oxygenation in saturated carbon with full control of regioselectivity and stereoselectivity. DOI: http://dx.doi.org/10.17807/orbital.v7i4.728